2012
DOI: 10.1007/s10856-012-4554-1
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan films: crosslinking with EDTA modifies physicochemical and mechanical properties

Abstract: The present study was aimed to develop chitosan-EDTA films and evaluate their physico-chemical and mechanical properties. The physical properties suggested lowest swelling, volume and volume index of films prepared by employing equal weight of chitosan (CH) and EDTA (1.5% w/v). The CH:EDTA film (1:l, on weight basis) showed minimum contact angle, work of adhesion and high negative spreading coefficient indicating lipophilic behavior of film. Further, the FTIR and DSC analysis suggested maximum crosslinking den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Despite few reports on the formation of conjugate material between chitosan and EDTA, there is no information in the published literature about the nature of the bond formed and the chemistry of this reaction (Bernkop-Schnurch & Krajicek, 1998;ElSharif & Hussain, 2011a;Loretz & Bernkop-Schnuerch, 2006;Singh, Suri, Tiwary, & Rana, 2012b). Hence, it can be surmised that the formation of distinct chemical bonds between chitosan and EDTA has not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite few reports on the formation of conjugate material between chitosan and EDTA, there is no information in the published literature about the nature of the bond formed and the chemistry of this reaction (Bernkop-Schnurch & Krajicek, 1998;ElSharif & Hussain, 2011a;Loretz & Bernkop-Schnuerch, 2006;Singh, Suri, Tiwary, & Rana, 2012b). Hence, it can be surmised that the formation of distinct chemical bonds between chitosan and EDTA has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan-EDTA conjugate is used in pharmaceutical field as topical application gel (Valenta, Christen, & Bernkop-Schnürch, 1998b). It has also been shown that chitosan-EDTA conjugates, prepared by using EDTA to crosslink, improves the flexibility of chitosan films and decreases the hardness thus facilitating better controlled and sustained delivery system (Singh, Suri, Tiwary, & Rana, 2012a). Chitosan-EDTA derivatives have been developed as promising candidates for the treatment of bacterial and fungal infections (El-Sharif & Hussain, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Wa values of OC3 film was found to be significantly (p < 0.05) different with respect to those of other films in all the buffers (Table 1). Negative value of spreading coefficient results in the formation of globule rather than film of liquid over a film surface [16]. Thus, the spreading coefficient signified comparatively less water-loving character of all the film surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Spreading coefficient of all the film surfaces was found to be negative. Negative value of spreading coefficient is known to result in the formation of globule rather than film of liquid over a film surface (Singh, Suri, Tiwary, & Rana, 2012). Hence, the values of spreading coefficient indicated relatively less hydrophilic character of all the film surfaces.…”
Section: Physical Performance Of Chebfg Filmsmentioning
confidence: 99%